Help my unbelief: James Joyce and religion - Lernout, Geert (Continuum, 2010)
A careful study of Joyce's published and unpublished writings reveals that throughout his career as a writer he rejected the church in which he had grown up. As a result, Geert Lernout argues that it is misleading to divorce his work from that particular context, which was so important to his decision to become a writer in the first place. --from publisher description